Transparency and Corporate Governance: Analysis of Factors Affecting Transparency and Its Effect on Market Valur of The Firm - DWI NOVI KUSUMAWATI; BAMBANG RIYANTO LS (The Indonesian Journal of Accounting Research, 2013)
This research has 2 models. The first model aims to investigate factors affecting the level of Good Corporate Governance (GCG) transparency in annual reports. Factors being predicted are firm’s specific characteristics and commissionaire characteristics. The second model aims to test empirically whether investors value that GCG transparency, which is reflected in the market value of firms. Moreover, the last model also investigates whether investors also consider other corporate governance variables, such as board characteristics.GCG transparency level is measured using 161 items recommended by GCG Codes, which are developed by KNKCG (2001). The statistical method being used is multiple regression analysis. The result shows that firm’s specific characteristics and commissionaire characteristics could affect the GCG transparency level, except for industry and cross-directorships variables. The GCG transparency level is also responded by the market, together with board characteristics, one of the other corporate governance variables.